Leadership behaviors of school principals in relation to teacher job satisfaction in north Cyprus - Sancar, Mine (Elsevier Science Bv, 2009)
This study determines leadership behaviors of public school principals as perceived by public school teachers in relation to teacher job satisfaction in Northern Cyprus. Teachers' perceptions of their school principals' leadership behavior was measured by the Leadership Behavior Description Questionnaire (LBDQ). Teachers' expressed job satisfaction level was measured by the Mohrman-Cooke-Mohrman Job Satisfaction Scales (MCMJSS). A Linear Regression analysis proved a significantly positive relationship between school principals' perceived 'consideration' behavior and teachers' expressed job satisfaction. However, there was no significant relationship between school principals' perceived 'initiation of structure' behavior and expressed teachers job satisfaction levels. (C) 2009 Elsevier Ltd. All rights reserved
World Conference on Educational Sciences -- FEB 04-07, 2009 -- Nicosia, CYPRUS
Keywords: School Principals; leadership; behavior; 'consideration'; 'initiation of structure'; job satisfaction